2017
DOI: 10.1016/j.hrmr.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impacts of team type and design on virtual team processes

Abstract: While much is known about virtual team processes and outcomes, the literature relies on a variety of team configurations and types (including student versus organizational samples, shortterm versus long-term teams, functional versus project-based teams, and teams with various task types) yet has not systematically examined how these differences impact team processes. This is important because much of the virtual teams research has been based on student samples, which are easier to access and control, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 103 publications
7
94
0
2
Order By: Relevance
“…Teams that trust each other perform better (Gibbs et al, 2017;Liao, 2017). By building confidence that colleagues will do what they say, and being honest when they can't, individuals collaborate more effectively and stave off duplicated work (Liao, 2017;Malhotra et al, 2007;Neeley, 2015;Peters and Manz, 2007;Schulze and Krumm, 2016).…”
Section: Build Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Teams that trust each other perform better (Gibbs et al, 2017;Liao, 2017). By building confidence that colleagues will do what they say, and being honest when they can't, individuals collaborate more effectively and stave off duplicated work (Liao, 2017;Malhotra et al, 2007;Neeley, 2015;Peters and Manz, 2007;Schulze and Krumm, 2016).…”
Section: Build Trustmentioning
confidence: 99%
“…As we've discussed, different mediums of communication involve varying degrees of virtuality and therefore information content. Intentionally thinking about the benefits and detriments of a communication medium before using it at least improves employee awareness of repercussions, and at best increases shared understanding and communicative efficiency (Gibbs et al, 2017;Larson and DeChurch, 2020;Martins et al, 2004). How likely are the parties to understand one another?…”
Section: Communicate Intentionallymentioning
confidence: 99%
“…Interestingly, a great deal of research on virtual teams has been conducted in lab settings or with students in temporary teams, with much less research conducted in organizational settings. Three recent reviews have found significant difference in outcomes depending on the type of virtual team and the research design [28][29][30]. Results from research that uses student or lab-based teams, which do not have managers with formal, organizational authority, may not generalize well to organizational settings, particularly where questions of organizational control are concerned.…”
Section: Control In Distributed Teamsmentioning
confidence: 99%
“…Understanding the role of culture is relevant, and even critical, to software teams because they are almost all increasingly being composed with multi-national members [17,18]. Furthermore, information systems (IS) academic programs predominantly use teams for coursework and general learning [19], and they aspire to be composed of students from diverse cultural backgrounds.…”
Section: Introductionmentioning
confidence: 99%